Coronary and cardiothoracic critical care breakthroughs in research and practice (Critical explorations., 2019)
"This book is an essential reference source for the latest scholarly material on emerging strategies and methods for delivering optimal healthcare for those with coronary and cardiothoracic diseases. It also examines the latest techniques and methods used in cardiovascular care"--Provided by publisher